Acceleration of the pre-oxidation process by tuning the degree of sulfurization for promoted oxygen evolution reaction - Xie, Junfeng; Dong, Changgang; Li, Jiechen; Guo, Min; Zhao, Ying; Kang, Luyao; Gao, Wen; Lei, Fengcai; Tang, Bo (Chemical communications (Cambridge, England), 2022)
In this work, Co-based nanocatalysts with variable degrees of sulfurization (DoS) were fabricated for the oxygen evolution reaction (OER). The partially sulfurized catalyst with a medium DoS could exhibit a promoted pre-oxidation process, leading to a highly efficient and ultrastable OER performance. In this work, Co-based nanocatalysts with variable degrees of sulfurization (DoS) were fabricated for the oxygen evolution reaction (OER).